Scenarios for the Integration of Virtual Exchange in Higher Education - Giralt, Marta; Betts, Alicia; Pittarello, Sara; Stefanelli , Cristina (Journal of International Students, 2022)
This paper describes the results of the analysis carried out within the Erasmus+ FRAMES project (https://frames-project.eu/) which collected and analysed Virtual Exchange (VE) case studies building upon desk research and through an open survey, so as to identify and describe various scenarios of accredited VEs. By using a qualitative methodology based on pattern matching analysis, collected cases were aggregated into four scenarios to be potentially used by a variety of European Higher Education Institutions (HEIs): VE as a preparatory or follow-up activity to physical mobility (blended mobility); VE as an intertwined component of physical mobility (blended mobility); VE as a stand-alone learning activity; VE as a component of a course. The main conclusions and recommendations revolve around the need to expand the number of potential scenarios across all disciplines and contexts and the urge to train academic as well as administrative staff to facilitate the integration of VE in HEIs.